Integrated teaching in primary schools: A systematic review of current practices, barriers, and future developments - Giang Thi Chau Nguyen; Dao Thi Thai (Institute of Advanced Engineering and Science, 2023)
Recent years have seen a rise in the use of integrated teaching in many nations across the globe due to the vital role it plays in the delivery of primary education programs that focus on the growth of students’ abilities. However, a comprehensive review of integrated classroom practices in elementary schools has yet to be conducted, making it difficult for interested readers to make education decisions about entering the sector or for established experts to keep up with the latest developments. To fill this gap, we performed a meta-analysis using the PRISMA procedure and a comprehensive literature search. Following the PRISMA guidelines, the study analyzed 24 publications on integrated teaching in primary school that appeared in Scopus and Google Scholar between 2014 and 2022. The study used text analysis and synthesis to highlight active nations, extracted keywords, drawing obstacles and challenges, and future research opportunities. The result reported 13 types of obstacles and challenges that need to be overcome in the long run. As such, five research directions were compiled based on prior publications, namely as teachers’ training program, integrated teaching materials, integrated teaching models, school policies and other interventions, and others. Interested readers, prospective researchers and policymakers could benefit from these findings by tackling existing issues or investigating recommended research directions.